Datos de investigación del artículo Unravelling the origin of the brown hyena (Parahyena brunnea) and its evolutionary and paleoecological implications for the Pachycrocuta lineage - Pérez-Claros, Juan Antonio (Coquina Press, 2024)
Measurements, ages and references of the specimens analyzed.
Keywords: Paleobiogeografía; Hienas - Evolución; Brown hyena evolution; Pliocrocuta; Pachycrocuta; Parahyaena; Paleobiogeography; Ecomorphology